Ensuring sustainability: a preliminary study of environmental management accounting in Malaysia - Sulaiman, Maliah; Mokhtar, Norsyahida (Society for Alliance, Fidelity and Advancement, 2012)
Our study on environmental management accounting focused on three pertinent issues: the extent companies in Malaysia implement EMA, the association between environmental management accounting (EMA) and environmental reporting (ER) and the perceptions of management towards the development of EMA. Data was grated through a postal questionnaire survey of 154 companies listed on the Main Board of Bursa Malaysia. Of the 19 companies that responded, only 8 reported that they have proper accounting systems to handle environmental issues. Respondents who said they have EMA, tended to disclose environmental information in their annual reports. On respondents' perception regarding the importance of EMA, the results indicate that most respondents agreed that EMA assists companies in generating environmental information. Despite the advantage of EMA in assisting companies to generate environmental information, the respondents felt that EMA development should not be compulsory for all industries. More importantly, they believed that only industries whose activities impact on the environment should implement EMA.